DN 9693: A Phosphodiesterase Inhibitor with a Platelet Membrane Effect - Jackson, C; Ball, J; Peel, J; Lawry, J; Greaves, M; Preston, F E (Thrombosis and Haemostasis, 1989)
We have examined the in vitro effects of DN 9693 (piperidinylimidazo-quinazolinone) on various aspects of platelet reactivity. Our results are consistent with its known function as a phosphodiesterase inhibitor in that it increased platelet cyclic AMP, particularly in conjunction with an adenylate cyclase stimulator, and exerted a profound inhibitory effect on platelet aggregation responses to a variety of agonists. DN 9693 also inhibited ristocetin-induced platelet agglutination (RIPA). We therefore examined its effect on ristocetin co-factor assays and on the binding of a monoclonal antibody (McAb) to platelet membrane glycoprotein lb (GPIb). The drug inhibited the binding of the monoclonal antibody in a dose-dependent manner. This suggests an effect of the drug on the platelet surface membrane with reduced expression of GPIb. Our results indicate that in addition to its anticipated inhibitory effect on platelet aggregation, DN 9693 may also inhibit platelet adhesion.
Keywords: DN 9693; Phosphodiesterase inhibitor; Platelet membrane glycoprotein Ib